Interrupting Institutional Heteronormativity: School Counsellors’ Role in Advocating for Gender and Sexually Diverse Students - Surette, Tanya E. (Canadian Journal of Counselling and Psychotherapy, 2019)
Many gender and sexually diverse students continue to view their schools as a hostile and oppressive environment. The focus in research has shifted more recently from individualizing this problem to understanding the complex systemic and institutional contributors to the ongoing marginalization of this population. As an integral part of the school system, school counsellors are uniquely positioned to offer important individual- and group-level supports to these students. Using narrative interviewing, this qualitative study provides an opportunity to visit the lived experiences of 6 current gender and sexually diverse high school students and their encounters with heteronormativity at school. Their stories offer insights into factors contributing to their distress and demonstrate stress-ameliorating factors that could be used to guide school counsellors who advocate for the safety and inclusion of students with diverse sexual orientations and gender identities.